2014
DOI: 10.1177/0333102414520763
|View full text |Cite
|
Sign up to set email alerts
|

Status migrainosus and migraine aura status in a French tertiary-care center: An 11-year retrospective analysis

Abstract: SM and MAS are rare. Our results highlight a high rate of relapse and a similar frequency of migraine attacks before and after SM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 8 publications
2
27
0
1
Order By: Relevance
“…10,11 SM is a debilitating complication of migraine with or without aura that lacks clear epidemiologic data. A recent 11-year retrospective analysis of a French tertiary headache center reported a 3% prevalence of SM, 6 while a 2006 multicenter study of 253 patients with migraine reported that 24.3% of those with aura and 20.6% of those without aura experienced head pain for more than 72 hours. 12 SM is thought to occur more frequently in those with episodic migraine (less than 15 headache days per month).…”
Section: Expert Opinionmentioning
confidence: 99%
See 3 more Smart Citations
“…10,11 SM is a debilitating complication of migraine with or without aura that lacks clear epidemiologic data. A recent 11-year retrospective analysis of a French tertiary headache center reported a 3% prevalence of SM, 6 while a 2006 multicenter study of 253 patients with migraine reported that 24.3% of those with aura and 20.6% of those without aura experienced head pain for more than 72 hours. 12 SM is thought to occur more frequently in those with episodic migraine (less than 15 headache days per month).…”
Section: Expert Opinionmentioning
confidence: 99%
“…A case report of MRI and PET scan of the brain during SM suggests that SM can be associated with vasogenic cerebral edema. 6 A case describing persistent migrainous vertigo possibly triggering cephalic SM suggests that stimulation of the vestibular system can trigger migraine attacks and bouts of SM. Emotional stress, depression, and med-ication overuse are among the most commonly reported, 2,6 and menstruation was found to be a precipitating factor in 31.3% of women with SM.…”
Section: Expert Opinionmentioning
confidence: 99%
See 2 more Smart Citations
“…All patients were female and had a history of migraine with aura. Mean duration of aura status was 4 weeks, 3 of these 4 patients had further episodes of aura status and 2 responded to treatment with lamotrigine, although separating natural history must be challenging here. A history of migraine with aura seems to be prerequisite for this condition, but it remains unclear why some patients develop aura status when most patients do not.…”
Section: Migraine Aura Statusmentioning
confidence: 99%